Simulation-based Optimization of Advanced Mixing Elements on Single Screw Extruders - Moritzer, Elmar; Wittke, M. (77th Annual Technical Conference of the Society of Plastics Engineers (ANTEC))

Spritzgießwerkzeuge mit Heatpipe-Temperierung - Moritzer, Elmar; Kartelmeyer, S.; Hüttemann, B.; Jaroschek, C. (26. Fachtagung über Verarbeitung und Anwendung von Polymeren)

Untersuchung der Verbundhaftung zwischen spritzgegossenen TPUs und einer reaktiven, gießfähigen Polyurethanmasse - Moritzer, Elmar; Jilg, J.; Sibbe, N. (PU MAGAZIN)

Vortrag „Aufschmelzen“ Optimierter Betrieb und Scale-up von Doppelschnecken-Extrudern - Schöppner, Volker; Westhues, K. (VDI Wissensforum)

Zur Wirkung dehnströmungsinduzierender Spritzgießdüsen für glasfaserverstärktes Polypropylen im Sonderverfahren der Spritzgießdirektcompoundierung (SGDC) - Moritzer, Elmar; Jilg, J. (26. Fachtagung über Verarbeitung und Anwendung von Polymeren)

Effect of playing position and time on-court on activity profiles in german elite team handball - Büchel, Daniel; Jakobsmeyer, Rasmus; Döring, Michael; Adams, Michael; Rückert, Ulrich; Baumeister, Jochen (International Journal of Performance Analysis in Sport)

Understanding and Manipulation of Nanoparticle Contact Forces by Capillary Bridges - Schmid, Hans-Joachim; Grundmeier, Guido; Dörmann, Michael; Orive, Alejandro González; de los Arcos, Teresa; Torun, Boray (Particles in Contact)
Since, in the presence of humidity the inter-particle processes are dominated by capillary forces, a fundamental understanding of the water adsorption and the capillary bridge formation is very important. However, the adsorbed water structure and thus the capillary bridge formation is influenced by various parameters like the particle morphology (e.g. particle size, roughness) as well as the surface chemistry (surface energy, adsorbate structure) and therefore needs to be analyzed on a submicroscopic or even molecular basis. A multi-scale approach ranging from experiments on an individual particle level (AFM and liquid bridge simulation) and investigations on small particle ensembles (combined QCM-D/FTIR) up to macroscopic description of bulk behavior is presented in this chapter. In this context, the combined in situ QCM-D/FTIR experiments are bridging the gap between experiments on an individual particle level and macroscopic bulk behavior. Variation of surface chemistry by means of adsorption of functional organic molecules allows for the correlation of macroscopic particle behavior to nanoscopic effects like the presence and structure of adsorbate layers as well as the formation of capillary bridges while keeping the disperse properties constant. Besides extensive experimental work, simulations of capillary bridges formed by condensation from humid air are presented. It is clearly shown that well known approximations which have been introduced for micron-sized particles are not valid any more for nano-scaled particles. The forces between nanoparticles by static liquid bridges and their dependency on particle size, contact angle, humidity and interparticle distance are discussed in detail. Furthermore, capillary forces during separation of particles are studied thoroughly and a constitutive law based on a contact stiffness allows the transfer to DEM simulations of wet powders. Finally, it is demonstrated by comparison to Molecular Dynamics simulations, that the used continuum approach to simulate capillary bridges might even be used down to particle sizes of a few nanometers, if some additional effects are considered correctly.

Characterisation of fabrication inhomogeneities in Ti:LiNbO3 waveguides - Santandrea, Matteo; Stefszky, Michael; Roeland, Ganaël; Silberhorn, Christine (New Journal of Physics)

General framework for the analysis of imperfections in nonlinear systems - Santandrea, Matteo; Stefszky, Michael; Silberhorn, Christine (Optics Letters)

Fabrication limits of waveguides in nonlinear crystals and their impact on quantum optics applications - Santandrea, Matteo; Stefszky, Michael; Ansari, Vahid; Silberhorn, Christine (New Journal of Physics)

Counter-propagating photon pair generation in a nonlinear waveguide - Luo, Kai-Hong; Ansari, Vahid; Massaro, Marcello; Santandrea, Matteo; Eigner, Christof; Ricken, Raimund; Herrmann, Harald; Silberhorn, Christine (Optics Express)

Quasiprobability distributions for quantum-optical coherence and beyond - Sperling, Jan; Vogel, W (Physica Scripta)

Measuring coherence of quantum measurements - Cimini, Valeria; Gianani, Ilaria; Sbroscia, Marco; Sperling, Jan; Barbieri, Marco (Physical Review Research)

What can single photons do what lasers cannot do? - Rezai, Mohammad; Sperling, Jan; Gerhardt, Ilja (Quantum Science and Technology)

Benchmarking of Gaussian boson sampling using two-point correlators - Phillips, D. S.; Walschaers, M.; Renema, J. J.; Walmsley, I. A.; Treps, N.; Sperling, Jan (Physical Review A)

Photonic quantum walks with four-dimensional coins - Lorz, Lennart; Meyer-Scott, Evan; Nitsche, Thomas; Potoček, Václav; Gábris, Aurél; Barkhofen, Sonja; Jex, Igor; Silberhorn, Christine (Physical Review Research)

Detailed study of Gaussian boson sampling - Kruse, Regina; Hamilton, Craig S.; Sansoni, Linda; Barkhofen, Sonja; Silberhorn, Christine; Jex, Igor (Physical Review A)

Eigenvalue measurement of topologically protected edge states in split-step quantum walks - Nitsche, Thomas; Geib, Tobias; Stahl, Christoph; Lorz, Lennart; Cedzich, Christopher; Barkhofen, Sonja; Werner, Reinhard F; Silberhorn, Christine (New Journal of Physics)

A high dynamic range optical detector for measuring single photons and bright light - Tiedau, Johannes; Meyer-Scott, Evan; Nitsche, Thomas; Barkhofen, Sonja; Bartley, Tim J.; Silberhorn, Christine (Optics Express)

Inklusiver Unterricht aus Sicht von Grundschullehrkräften. Die Bedeutung von persönlichen Ressourcen - Görel, Gamze